Gynecomastia induced by H1-antihistamine (ebastine) in a patient with idiopathic anaphylaxis - Jung, Hwa Sik (Asia Pac Allergy, 2015)
H1-antihistamine is generally a well-tolerated and safe drug. However, in resemblance with all other drugs, H1-antihistamines can also prompt adverse drug reactions (ADRs). We recently encountered the very unusual ADR of H1-antihistamine-induced gynecomastia. A 21-year-old man with idiopathic anaphylaxis was treated with ebastine (Ebastel), a second-generation H1-antihistamine, for the prevention of anaphylaxis. Three months later, the patient remained well without anaphylaxis, but had newly developed gynecomastia. Because anaphylaxis recurred after the cessation of H1-antihistamine, the preventive medication was changed to omalizumab. A few months later, his gynecomastia had entirely disappeared. Physicians should be aware of this exceptional ADR of H1-antihistamine.